Dinamika Formalisasi Syariat Islam di Indonesia Dalam Konteks Pancasila - Dalmeri, Dalmeri (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2023)
This article describes that Islamic law doesn’t need formalizing into Pancasila because of the Indonesian condition that has many differences such as religion, culture, etc. But, on another side many policies that are established and applied in Indonesia result from the adaptation of Islamic law. One of the examples is Pancasila. It contains Islamic laws soul, for example, the first sila of Pancasila (Ketuhanan yang Maha Esa). That sila is the source of other sila in Pancasila. So, without the legitimation of Pancasila, Indonesian can apply syariat Islam in the Indonesian lifestyle. We hope to use our regulation to recover the law’s condition of Indonesia.